Clay minerals at DSDP Sites 71-511 and 71-513 - Pyotr P Timofeev; N V Renngarten; Mikhail A Rateev (PANGAEA, 1983)
The distribution of clay minerals, determined by X-ray diffraction, is given for Jurassic to Holocene sediments recovered at DSDP Sites 511 and 513 in the Southwest Atlantic. These data, plus the lithologic and paleoenvironmental information gathered by the shipboard scientists, are used to subdivide the sedimentary sequence into genetic lithologic facies labeled series, seven for Site 511 and two for Site 513. Sediments of these series reflect the main historical and paleoenvironmental events which other means of study have determined to affect this region; particularly important was the opening of the South Atlantic during the Early Cretaceous.
Supplement to: Timofeev, PP et al. (1983): Lithologic facies and clay mineral assemblages in Mesozoic and Cenozoic sediments recovered by Deep Sea Drilling Project Leg 71 in the South Atlantic. In: Ludwig, WJ; Krasheninnikov, VA; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 71, 377-388, https://doi.org/10.2973/dsdp.proc.71.115.1983